2002
DOI: 10.1002/1521-3773(20020517)41:10<1699::aid-anie1699>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

How Attractive is Bromine as a Protecting Group in Aromatic Chemistry?

Abstract: The reversibility of electrophilic bromination of aromatic compounds has been known for a long time, but the possibility of using bromine as a protecting group in aromatic or heterocyclic chemistry has now been shown for the first time (see scheme for an example). Compared with typical protective groups (SO3H, COOH, NH2, CHMe2, CMe3) bromine offers many advantages; a decisive aspect for its successful application is the choice of optimized reaction conditions which are predictable from the reaction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…The mechanism of BDE transformation by reductive dehalogenation was similar to the effects observed previously for PCBs with CCA s [23], but the transformation was faster in our experiments. Some minor differences might be caused by the different experimental design, but the role of bromine as a leaving group of aromatics [30] different from that of chlorine might be an important issue. However, the transformation of BDEs was much lower than that for toxaphene, which was transformed by more than 90% after 6 h [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of BDE transformation by reductive dehalogenation was similar to the effects observed previously for PCBs with CCA s [23], but the transformation was faster in our experiments. Some minor differences might be caused by the different experimental design, but the role of bromine as a leaving group of aromatics [30] different from that of chlorine might be an important issue. However, the transformation of BDEs was much lower than that for toxaphene, which was transformed by more than 90% after 6 h [25].…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast to the results of previous studies with PCBs [23] and toxaphene [25], in which no transformation was found with titanium(III)citrate alone. The different behavior of BDEs most likely results from the fact that bromine is a good leaving group in aromatic compounds [30], in contrast to chlorine. Because the effect without corrinoid was low compared to that with the use of corrinoids, we did not correct our results for this effect.…”
Section: Methodsmentioning
confidence: 99%
“…In order to favor the construction of the required isochroman bearing a contiguously substituted aromatic moiety, the aldehyde 5 was first brominated, [21] furnishing 6 in 93 % yield, [22] as depicted in Scheme 1. Next, olefination of bromoaldehyde 6 with MeCHϭPPh 3 afforded an inseparable mixture of isomeric β-methylstyrene derivatives (E/Z approx.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding this third hypothesis, Effenberger and others have shown that electron-rich bromoarenes reversibly isomerize in the presence of Lewis acids or HBr. 12 …”
mentioning
confidence: 99%
“…Although not observed directly, the evidence implicates the first scenario and the formation Br 2 , because HCl (which could effect processes 2 and 3) does not induce rearrangement. It has been shown that both HBr and HCl effect bromoisomerization of similarly electron-rich arenes (bromocresols and dimethylanilines) though arenium cation intermediates, 12 and that the rate was dependent on the nucleophilicity of the bromine-abstracting nucleophile; consequently, HCl was substantially slower. Accordingly, rearrangement in the presence of HCl should be observed if either chloride, the aniline nitrogen, or the 4-carbon was the bromine-abstracting nucleophile, but this was not the case (Table 1, entry 4, and Table 2, entry 3); therefore, chloride, nitrogen, and carbon nucleophiles are not competent.…”
mentioning
confidence: 99%